Actin cytoskeleton remodeling at the cancer cell side of the immunological synapse: good, bad, or both? - Ockfen, Elena; Filali, Liza; Pereira Fernandes, Diogo; Hoffmann, Céline; Thomas, Clément (Frontiers in Immunology, 2023)
Cytotoxic lymphocytes (CLs), specifically cytotoxic T lymphocytes and natural killer cells, are indispensable guardians of the immune system and orchestrate the recognition and elimination of cancer cells. Upon encountering a cancer cell, CLs establish a specialized cellular junction, known as the immunological synapse that stands as a pivotal determinant for effective cell killing. Extensive research has focused on the presynaptic side of the immunological synapse and elucidated the multiple functions of the CL actin cytoskeleton in synapse formation, organization, regulatory signaling, and lytic activity. In contrast, the postsynaptic (cancer cell) counterpart has remained relatively unexplored. Nevertheless, both indirect and direct evidence has begun to illuminate the significant and profound consequences of cytoskeletal changes within cancer cells on the outcome of the lytic immunological synapse. Here, we explore the understudied role of the cancer cell actin cytoskeleton in modulating the immune response within the immunological synapse. We shed light on the intricate interplay between actin dynamics and the evasion mechanisms employed by cancer cells, thus providing potential routes for future research and envisioning therapeutic interventions targeting the postsynaptic side of the immunological synapse in the realm of cancer immunotherapy.This review article highlights the importance of actin dynamics within the immunological synapse between cytotoxic lymphocytes and cancer cells focusing on the less-explored postsynaptic side of the synapse. It presents emerging evidence that actin dynamics in cancer cells can critically influence the outcome of cytotoxic lymphocyte interactions with cancer cells.